2011
DOI: 10.1007/s00294-011-0347-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interactions between POB3 and the acetylation of newly synthesized histones

Abstract: Pob3p is an essential component of the S. cerevisiae FACT complex (yFACT). Several lines of evidence indicate that the yFACT complex plays an important role in chromatin assembly including the observation that the pob3 Q308K allele is synthetically lethal with an allele of histone H4 that prevents the diacetylation of newly synthesized molecules. We have analyzed the genetic interactions between the Q308K allele of POB3 and mutations in all of the sites of acetylation that have been identified on newly synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…6C). This physical interaction was consistent with the recently reported genetic interactions that suggest a role for the yFACT complex in guiding newly synthesized histones into chromatin (29). The unique H3K56ac specificity of Rtt106 suggested that the modification-independent recognition surface would be functionally conserved between Pob3 and Rtt106, whereas the H3K56ac-specific recognition surface would be important only for Rtt106-histone binding.…”
Section: Rtt106:h3 Binding Was Required For the Delivery Of H3k56ac Dsupporting
confidence: 89%
See 1 more Smart Citation
“…6C). This physical interaction was consistent with the recently reported genetic interactions that suggest a role for the yFACT complex in guiding newly synthesized histones into chromatin (29). The unique H3K56ac specificity of Rtt106 suggested that the modification-independent recognition surface would be functionally conserved between Pob3 and Rtt106, whereas the H3K56ac-specific recognition surface would be important only for Rtt106-histone binding.…”
Section: Rtt106:h3 Binding Was Required For the Delivery Of H3k56ac Dsupporting
confidence: 89%
“…6A). Rtt106 and Pob3 both interact with histones H3/H4, and a mutant allele of pob3 interacts genetically with mutations on H3 at K56 (7,29). Therefore, we determined whether the histone-binding mechanism and acetyl-lysine specificity were conserved between these structurally similar chromatin-associated proteins.…”
Section: Rtt106:h3 Binding Was Required For the Delivery Of H3k56ac Dmentioning
confidence: 99%
“…These results were confirmed by confocal immunofluorescence analyses in which a uniform increase in γH2AX was observed 6 h after NCS treatment in SUPT16H-knockdown cells in yeast. 35 Furthermore, H2Bub1 was shown to cooperate with FACT during transcriptional elongation, 23 whereby it was proposed that FACT catalyzes an exchange of histone H2A-H2B dimers in an H2Bub1-dependent manner. 36 Based on the effects of RNF40 knockdown on H3K56ac, we hypothesized that a loss of H2Bub1 may lead to impaired histone exchange following DNA damage through decreased FACT recruitment.…”
Section: Resultsmentioning
confidence: 99%
“…Initial genetic studies in yeast using mutations that altered H4 lysines 5 and 12 to arginine indicated that the absence of this modification was well tolerated (30,31,66,67). More-recent studies have shown that the H4 K5,12R allele can have a significant effect on cell viability in strain backgrounds that have mutations in the Pob3p subunit of the yeast FACT (facilitates chromatin transcription) complex (28,68). These studies suggest that FACT may be involved in nucleosome assembly but, given the multifunctional nature of the FACT complex, do not shed light on the specific function of H4 lysine 5/12 acetylation.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in yeast that alter H4 lysine 91 cause severe defects in silent chromatin formation and sensitivity to DNA-damaging agents. Consistent with a role for H4 lysine 91 acetylation in chromatin assembly, genetic analysis of these mutations indicates that this modification functions in common pathways with the histone chaperones Asf1 and CAF-1 in the context of DNA repair (23,28). A histone acetyltransferase, termed HAT4, that appears to be responsible for this modification was recently isolated from mammalian cells.…”
mentioning
confidence: 99%